Evaluation of Food Security Area of East Java Province Using Fuzzy C-Means (FCM) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - Yuniar Farida; Ghina Salsabila Firdaus; Ahmad Teguh Wibowo; Silvia Kartika Sari; Latifatun Nadya Desinaini (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2023)
The formation of quality human resources cannot be separated from food, as nutritional intake affects human performance and health. As time increases, the number of residents increases to increase food needs. The ability of a region to meet food needs in its territory is different from other regions. This study aims to classify regions in East Java Province based on food security and determine areas with the best and lowest food security. The method used is the Fuzzy C-Means (FCM) and TOPSIS methods.This research uses criteria based on the Food Security Index compiled by the Food Security Agency. The results of regional clustering using FCM selected the best cluster using three clusters for all requirements, except in food utilization in the city using five clusters. Furthermore, from the clustering results, clustering and cluster members use TOPSIS and produce Magetan regency and Madiun city as areas with the highest food security. At the same time, the lowest food securities are Probolinggo regency and Kediri city.